Advances in Cross-Cultural Decision Making Proceedings of the AHFE 2016 International Conference on Cross-Cultural Decision Making (CCDM), July 27-31,2016, Walt Disney World®, Florida, USA - Schatz, Sae.; Hoffman, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book reports on the latest advances in understanding human cognition and its interplay with various cultural constructs, such as geographical, historical, sociological, and organizational cultures. It addresses researchers, scholars, and industry practitioners from diverse backgrounds, including sociology, linguistics, business, military science, psychology, human factors, neuroscience, and education. The book covers a wealth of topics, such as the analyses of historical events and intercultural competence, commercial applications of social-cultural science, the study of decision-making similarities (and differences) across cultures, Human, Social, Cultural Behavioral (HSCB) modeling and simulation technology, as well as social networks and studies on group communication. It also reports on real-world case studies relevant to cross-cultural decision making. The book aims at combining neurocognitive studies with studies from other relevant disciplines to develop a more holisticunderstanding of the decisions that people, groups, and societies make to improve the ability to forecast and plan for the future. The book is based on the AHFE 2016 International Conference on Cross-Cultural Decision Making (CCDM), held on July 27-31, 2016, in Walt Disney World®, Florida, USA.
Dynamic PMESII Modeling in Complex Environments Expeditionary modeling for population-centric operations in Megacities: Some Initial Experiments -- Cross-Cultural Comparisons in Business, Education, and Outlook Difference Analysis of Impression on Japan from Chinese Students with Different Education Stages -- Human-Machine Interactions and Tools Beyond Culture in the Cockpit: Implications for CRM Training -- Foreign Relations: Tools and Analyses Evaluating Automatic Learning of Structure for Event Extraction -- Toward Culturally-Aware Systems -- Contemporary Defense Applications of Social Science Considering Culture In Contemporary Military InterventIons -- Sociocultural, Behavioral Modeling for Defense Applications: Theory and Practice. .
Keywords: Computational intelligence; User interfaces (Computer systems).; Human-computer interaction; Psychology, Experimental; Experimental economics; Operations research; Computational Intelligence; User Interfaces and Human Computer Interaction; Experimental Psychology; Experimental Economics; Operations Research and Decision Theory